Complications Following Surgical Correction of Medial Patellar Luxation in Small-to-Medium-Size Dogs - Rossanese, Matteo; German, Alexander J.; Comerford, Eithne; Pettitt, Rob; Tomlinson, Andrew; de Vicente, Felipe (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The main aim of this study was to describe complications in dogs weighing < 20 kg treated for medial patellar luxation and to determine risk factors associated with these complications.Materials and Methods Medical records were reviewed and cases were grouped based on four techniques of stabilization for the tibial tuberosity transposition (TTT). Variables including animal signalment, clinical presentation, TTT technique, other concurrent surgical techniques and associated complications were investigated. Multiple logistic regression was used to determine the association of the same variables with specific complications such as tibial tuberosity fractures or avulsions, patellar reluxation and implant-related complications.Results Of the 100 procedures performed, 37 suffered a complication. There were no significant differences in the overall complication rate between TTT stabilization techniques. Preservation of the tibial tuberosity distal cortical attachment was associated with a reduced risk of implant-related complications, whereas adding a medial release to the surgical techniques was associated with an increased risk of medial patellar reluxation. The type of trochleoplasty performed did not affect the complication rate.Conclusions In the current study, a high rate of complications was found in dogs < 20 kg undergoing medial patellar luxation surgery. Performing a medial release and preserving the distal cortical attachment of the tibial tuberosity were the only variables associated respectively with an increase and a reduction in the risk of postsurgical complications.
Keywords: medial patellar luxation; tibial tuberosity transposition; trochlear block recession; trochlear wedge recession; tension band wire